Materials at the Nanoscale - Kumar Mallik, Awadesh (IntechOpen, 2021)
Nanocrystals play very important roles in the interdisciplinary fields of biology, physics and chemistry. They are used for various applications, including to develop and formulate new drugs and vaccines to fight diseases and pandemics. This book contains nine chapters that discuss nanocrystals in electronics, medicine, the food industry, geology, and more.